Invention de soi et compétences à l'ère des réseaux sociaux - Daniel Apollon (Université de Provence, 2010)
Social media practices encourage new approaches and visions of competence focusing on the construction of individual biography and the "invention of oneself". The new "artful skills" of "produsers" address the need to invent individual and collective responses to the sense of alienating emptiness pervading postindustrial and posttraditional societies. Combining and submission and opposition to both structuring and alienating aspects of late modernity, these produsagers actualize various tricks, tactics and immemorial schemes already mapped by various authors before the Internet. On this backdrop the author proposes a broader reinterpretation of the concept of competence.